How workplace discipline, transformational leadership, and career development affect employee performance at the Royal Beach Hotel Seminyak Bali - Iwk Teja Sukmana; Ni Putu Adella Tika Pertiwi; I Ketut Sirna; Eko Sulistiyo; Putu Chris Susanto (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This study examines the impact of workplace discipline, transformational leadership, and career development on employee performance at a five-star hotel in Bali. The study was conducted at the Royal Beach Seminyak Bali, which is a part of Accor Group’s MGallery Collection of boutique hotels. The data was collected from 73 employees who were selected using a randomized sampling method using a close-ended questionnaire, which was then analyzed quantitatively using regression analysis. The results suggest that workplace discipline, transformational leadership, and career development positively affect employee performance (sig. of 0.038; 0.032; and 0.028 respectively [α < 0.05]). Meanwhile, the study also indicates that workplace discipline, transformational leadership, and career development simultaneously have positive effect on employee performance (F-count = 31.702, greater than F-table = 2.74, α < 0.01). This suggests that improvement in workplace discipline, transformational leadership, and career development, could positively affect employee performance at The Royal Beach Seminyak Bali.